Status of Girls under International Covenants: a Study of Advocacy of Child-Marriage - Anshor, Maria Ulfah (Yayasan Jurnal Perempuan, 2015)
In Beijing Platform Action (BPFA) in 1995, one of the twelve critical issues is the girl-child. Referring to the reality in many countries that girls from an early age are treated discriminately and harmfully into practices such as female genital mutilation, sex selection before the baby is born, even the killing of female infants, violence against girls, child marriage, sexual exploitation, sexual abuse, discrimination against girls in provision, protection, & participation and other discriminatory practices, such as regarding the health and welfare facilities for girls. This paper will examine Indonesia’s efforts to reduce the marriage of girls.